The Influence of Motivator Factors and Hygiene Factors on Job Satisfaction and Intention to Stay of Employees between the Directorate General of the Ministry of Trade - Muhammad Afief Amrullah; Yasmine Nasution (Green Publisher Indonesia, 2025)
The high level of job dissatisfaction and differences in intention to stay among employees in various directorates of the Ministry of Trade indicate the need for an in-depth analysis of the factors that influence job satisfaction and employee retention, especially in the context of the complex public sector. This study aims to analyze the factors that influence job satisfaction and intention to stay among State Civil Apparatus (ASN) in the Ministry of Trade of the Republic of Indonesia. Using a quantitative approach and survey method, this study integrates Herzberg's Two Factor Theory (Motivator Factors and Hygiene Factors) to explain the dynamics of employee retention. The variables studied include motivator factors, compensation systems, work-life balance, company culture, supervisors/management, job satisfaction, and intention to stay. Data were collected through questionnaires distributed to 226 ASN respondents in various work units of the Ministry of Trade. Data analysis was conducted using Partial Least Square Structural Equation Modeling (PLS-SEM) to test the relationship between variables. Of the total 16 hypotheses analyzed, 9 of them were supported in this study. This study found that motivator factors, work-life balance, corporate culture, and supervisor/management significantly increase job satisfaction, which in turn, together with work-life balance, directly increases the intention to stay. Furthermore, job satisfaction is proven to mediate the influence of motivator factors, work-life balance, and supervisor/management on the intention to stay. These findings provide practical implications for human resource management in the Ministry of Trade, especially in designing strategies to improve employee retention through increasing job satisfaction.